Impact of Antidepressant Treatment on Heart Rate Variability in Patients with Depression - A Cross Sectional Study - Raghav M V; Geetha A; Praveen Panchaksharimath; Nivetha Raj (Pharmacology and Clinical Pharmacy Research, 2023)
Heart rate variability (HRV) is a non-invasive index of cardiac autonomic regulation. HRV is reduced in depression, which indicates decreased Autonomic Nervous System flexibility. It is associated with an increase in the frequency of cardiac co-morbidities. Depression medications usually take six months for complete remission, but no data on patients on antidepressants for more than six months. Therefore, it becomes necessary to determine if anti-depressants have a better impact on HRV. The current study focused on analyzing the correction of HRV parameters after six months of antidepressant therapy. A cross-sectional study was conducted from February to September 2021 at the AFT lab inpatients. They were recruited from the Psychiatry department, Victoria Hospital, Bangalore Medical College and Research Institute, Bengaluru, Karnataka, India. The sample size was calculated to be 40 (20 Patients and 20 Healthy controls). AFT was done on all participants using Power Lab equipment and analyzed using Lab Chart 8 software. Heart rate variability parameters (AFT results) were analyzed using statistical software. The results with a p-value of >0.05% were considered statistically significant and taken up for the study. 55% of the patients with depression in our study were in the age group of 18-25 years, and the mean Ham-D (Hamilton Depression Rating Scale) score was found to be 9.8.  There is a reduction in autonomic function flexibility among patients who are on antidepressants when compared to healthy controls, even after six months of treatment. No conclusion could arrive on the class of antidepressant which was more beneficial owing to its effect on autonomic functions. Hence, randomized controlled studies comparing various classes of antidepressants to assess efficacy in reducing autonomic complications of depression should be taken up